Creating a Media Lab at the Universidad Nacional Mayor de San Marcos-P erú - Oyarce-Cruz, Jacqueline (2017)
The main objective of creating a Media Lab as specialized space was to study internet and other digital media in mass communication. A specific objective was to study and apply digital strategies to broadcast scientific contributions of the Universidad Nacional Mayor de San Marcos. It is an applied, cross-sectional study. It uses podcast, streaming and hypertext. As a result, the Media Lab UNMSM was created. Today is a Research Nucleus of the Universidad Nacional Mayor de San Marcos. A Media Lab enables students and professors to innovate with digital media. It also helps to spread scientific content among the community. It is the first Media Lab of the Peruvian university.